REVIEW OF ISLAMIC LAW OF THE WAGE SYSTEM LABOR : Study At The Adee Kak Nah Cake Production House Of Meuraksa Gampong, Meureudu District - Abdullah, Arifin; Akbar, Hajarul; Husna, Asmaul (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
The amount of wages should be known clearly by the workforce, but at the cake production house Adee kak Nah Gampong Meuraksa, Meureudu District, in practice there is no agreement regarding the amount of wages that will be received by the workers at the beginning of the contract between the employer and the workforce does not state how much the amount is the wages that will be given for the Adee cake pan that is produced, the pillars of ijarah in the wage system at the Adee cake production house have not been fulfilled, one of which is because it does not mention and explain the amount of wages that will be received. not infrequently there are differences in wages between one worker and another worker. Therefore, the author is interested in further researching the wage system that exists at Adee kak Nah's cake production house. The purpose of this study is to find out how the labor wage system is at the Adee kak Nah cake production house in the village of Meuraksa, and to find out how Islamic law reviews the labor wage system at the Adee kak Nah cake production house. This research is a qualitative research using a descriptive analysis research approach through interviews, observation, and documentation techniques. From the results of the research, the authors found that the wage system that existed at the Adee kak Nah cake production house was a piece wage system in which the wage system could be assigned to jobs that could be measured such as the amount of weight, number and area. If viewed from the point of view of the legal pillars of ijarah, the contract is canceled because there is one pillar that is not fulfilled. However, the practice of wage labor at the Adee kak Nah cake production house has become a custom and habit of the local community and contains benefits. Therefore, the practice of remuneration for labor at the Adee cake production house, sis. Well, this is permissible.